Estradiol Attenuates EGF-Induced Rapid uPAR Mobilization and Cell Migration via the G-protein-Coupled Receptor 30 in Ovarian Cancer Cells. Issue 2 (1st January 2009) - Henic, Emir; Noskova, Vera; Høyer-Hansen, Gunilla; Hansson, Stefan; Casslén, Bertil
Abstract : Epidermal growth factor (EGF) stimulates proliferation and migration in ovarian cancer cells, and high tumor expression of the EGF system correlates with poor prognosis. Epidermal growth factor upregulates urokinase plasminogen activator receptor (uPAR) on the cell surface via 3 distinct mechanisms: rapid mobilization of uPAR from detergent-resistant domains, increased mRNA, and decreased degradation. G-protein-coupled receptor 30 (GPR30) is a newly identified membrane estrogen receptor (ER). The objective of this study was to explore the effects of 17β-estradiol (E2 ) on uPAR expression and cell migration in ovarian cancer cells and further to identify the ER involved. We used 7 ovarian cancer cell lines, cell migration assay, cellular binding of 125 I-uPA, cellular degradation of 125 I-uPA/PAI-1 complex, enzyme-linked immunosorbent assay for uPAR, solid-phase enzyme immunoassay for ERα, and quantitative polymerase chain reaction. Estradiol attenuates the stimulatory effect of EGF on cell migration and uPAR expression. Specifically, E2 reduces the very rapid increase of detergent extractable uPAR, which occurs within minutes of EGF stimulation and probably represents mobilization of uPAR from detergent-resistant domains such as lipid rafts. Estradiol influenced neither the amount of uPAR mRNA nor the rate of uPAR degradation or solubilization. The nuclear ER antagonists ICI 182780 and tamoxifen, which are GPR30 agonists, as well as the specifically constructed GPR30 agonist G1, mimicked the effect of E2 on uPAR expression and cell migration. OVCAR-3 cells express mRNA for GPR30. Estradiol attenuates EGF-induced mobilization of ligated uPAR from detergent-resistant domains and subsequent migration in ovarian cancer cells. The response to various ER ligands indicates that this effect is mediated via the membrane ER GPR30.